FACTORS THAT SUPPORT AND INHIBIT THE LEVEL OF WOMEN'S PARTICIPATION IN CULTURAL DESTINATION DEVELOPMENT IN THE TRADITIONAL VILLAGES OF TAKPALA AND MONBANG - Desis Plantina Halena Mautuka; Antonius Koby (Peneliti.net, 2026)
The results of the study show that the level of women's participation is very low in decision-making, so that women in Takpala and Monbang Traditional Villages are forced to participate in tourism activities such as the formation of weaving, Sanggar groups and maintaining environmental cleanliness. Factors that encourage the progress of cultural tourism destinations such as women's self-awareness, family support and women's hopes and desires. Inhibiting factors such as the weak involvement of women in the development of cultural tourism destinations, lack of infrastructure to support women's activities in tourism, and patriarchal culture so that efforts to increase women's participation are to involve women in the decision-making process, implementation of decisions and supervision. It was concluded that the level of female participation was low because there are factors which hinders the level of participation so that there are efforts to increase it. women's participation rate. On the other hand, the government, Tourism Office and Culture Office need to collaborate and work together to conduct outreach. and training for women related to tourism as an activity that can support creativity, develop skills, create new innovations for women's groups in Takpala and Monbang Traditional Villages.